2016
DOI: 10.1097/acm.0000000000000977
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Open-Book and Closed-Book Examinations

Abstract: Given the data available, there does not appear to be sufficient evidence for exclusively using CBE or OBE. As such, a combined approach could become a more significant part of testing protocols as licensing bodies seek ways to assess competencies other than the maintenance of medical knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
116
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(174 citation statements)
references
References 1 publication
9
116
0
7
Order By: Relevance
“…were not able to conclude that ICEs should be the preferred examination method in health care professions [18].…”
Section: Introductionmentioning
confidence: 93%
“…were not able to conclude that ICEs should be the preferred examination method in health care professions [18].…”
Section: Introductionmentioning
confidence: 93%
“…Part of the explanation for the reduction in anxiety could be that OBA tends to lead to less cramming by students and subsequently to a more consistent learning environment (Green, Ferrante and Heppard 2016). Durning et al (2016) are however of the opinion that students may overestimate the reduction in anxiety. An expectation that lecturers will choose more difficult questions can increase anxiety in an OBA setting (Eilertsen and Valdermo 2000).…”
Section: Anxietymentioning
confidence: 98%
“…The literature study is presented under the headings of time, anxiety, examination performance and differences among courses and subjects. Having performed an extensive systematic literature review on peer-reviewed articles published up to 2014, Durning et al (2016) concluded that empirical literature comparing OBA to CBA in general is fairly limited.…”
Section: Literature Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Following an extensive systematic review, Durning et al (2016) concluded that empirical literature comparing OBA to CBA is fairly limited. Only a few studies comparing OBA to CBA in accounting education could be found.…”
Section: Introductionmentioning
confidence: 99%